JIWA MENURUT TERTULIANUS: SUATU POLEMIK FILOSOFIS - Edison R.L. Tinambunan (Studia Philosophica et Theologica, 2003)
Tertulian is the Latin father of the church who eradiated many writings; and “de Anima” is one of his important writing, which treats about soul. In this writing, Tertulian wrote his polemic with Platonism and Stoicism philosophy. Both philosophies have advantage and disadvantage. Tertulian as a philosopher and believer profits these philosophies of advantage and disadvantage in his polemic about soul with the philosophers. At the end of his polemic, he concludes that the both philosophies could be a great help for the teaching of soul, but also be a seed of heresy.